Информационно-коммуникационные технологии в образовании студентов специальности >>5В010900-Математика<< педагогического вуза - Каскатаева, Бакыткуль Р.; Баймулдина, Назира С. (Annales Universitatis Paedagogicae Cracoviensis | Studia ad Didacticam Mathematicae Pertinentia, 2017)
In the paper the authors discuss educational usefulness of special applied software (Mathematica) in the process of studying Mathematics at the pedagogical university. The authors also present the levels of thecompetences connected with using an educational electronic means, necessaryfor the students of mathematics.